Mutiny and maritime radicalism in the age of revolution a global survey - Anderson, Clare 1969- (International review of social history Special issue, 2013)
"This volume explores the transnational dimensions of mutiny and maritime radicalism during the great cycle of war and revolution that began in the mid-1750s and continued until the 1840s. The central theme of the volume is mutiny - its causes, frequency, forms, patterns and outcomes - charting, linking and comparing maritime insurrections in different oceans, on warships, merchant vessels and convict ships. The contributions concentrate on the mutineers themselves, their social composition, self-organisation, objectives and ideas"--Publisher description on Amazon (viewed 1/15/2014)